Effect of point distance and time exposure on mechanical properties of selective laser melted stainless steel 316 - Hasan, Rafidah; Abu Samah, Asa Fansuri; Shamsudin, Zurina (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigates the effect of point distance and time exposure on SLM stainless steel 316 and compare with standard conventional stainless steel 316. Nine specimens (VD2, VD3/VT1, and VT2) were fabricated using the SLM machine Renishaw RenAM 500E with parameters of 240 W laser power, 0.055 mm and 0.06 mm point distance, 80 µs and 90 µs time exposure, 0.11 mm hatch distance, 0.05 mm layer thickness, 67° scanning rotation between subsequent layers, and a stripe with a 5 mm width scanning strategy. The shape of the particle is almost spherical, and the range of particle diameters of metallic powder was 15-45 µm for the fabrication of SLM stainless steel 316. Three specimens of stainless steel 316 from a conventional plate were prepared using a laser cutting machine. Twelve specimens were tested with the Archimedes method using an MDS-300 densimeter for density measurement, surface roughness test using a non-contact profilometer for surface roughness measurement, ultrasonic test using Olympus Epoch 650 to determine sound velocity measurement, and three-point bending test using Instron 5585 to determine Young’s modulus value. In ultrasonic testing, results show that Young’s modulus value of VD3/VT1 (129.152 GPa) is more comparable to the standard Young’s modulus of stainless steel (193 GPa). This is due to a stable molten pool and coarse grain size which leads to an increase in density and sound velocity increase in SLM parts. In three-point bending testing, it is shown that Young’s modulus value of VD3/VT1 (126.825 GPa) is comparable with standard Young’s modulus value of stainless steel 316, due to the internal structure formed during the SLM process. From this study, it is shown that more analysis should be done to explore how point distance and time exposure can be factors that effect on mechanical properties.